The relationship of muscle functions with functional performances and kinesiophobia in older persons with low back pain / Nor Azizah Ishak - Ishak, Nor Azizah (2018)
This study aims to 1) compare muscle functions and functional performances among gender in institutionalized older persons with and without low back pain (LBP); 2) to determine the association between muscle functions and functional performances; 3) to determine the association between kinesiophobia with pain, muscle functions and functional performance in older persons with LBP. A cross-sectional study and correlation study involving older persons living in the public funded institutions was performed. Anthropometric characteristics (BMI, waist circumference) and functional performances (lower limb function, balance and mobility, hand function) were measured. The muscle functions (muscle strength of abdominal and back) were assessed using a Baseline® Mechanical Push Pull Dynamometer and muscle control (TrA and multifidus) was measured by using a pressure biofeedback Unit. The pain intensity and the level of kinesiophobia were measured using the Numerical Rating Scale and Tampa Scale of Kinesiophobia, respectively. Data were analyzed using the ANOVA, Pearson’s correlation, multiple linear regressions and multivariate linear regression. The results showed the functional performances did not show significant differences between females with and without LBP as well as males with and without LBP (p>0.05). For muscle functions, significant differences were found between females with and without LBP for abdominal muscle strength (p=0.006) and back muscle strength (p=0.07). Significant correlations were found between abdominal muscle strength and hand function (r=0.377), back muscle strength and hand function (r=0.396) in females with LBP, back muscle strength and lower limb function (r=0.393) in males with LBP, as well as multifidus control and lower limb function (r=0.363) in females with LBP (All, p<0.05). Regression analysis showed abdominal (p=0.041) and back muscle strength were significant predictors of hand function (p=0.049). Multifidus control was a significant predictor of lower limb function in the female with LBP (p=0.047). No significant correlations were found between kinesiophobia with pain and muscle functions (All, p>0.05). Kinesiophobia was significantly correlated with mobility and balance (p=0.038). Regression analysis showed that kinesiophobia was a significant predictor of mobility and balance (p=0.038). In conclusion, this study demonstrates that older women with LBP exhibit poorer muscle functions compared to older women without LBP. Muscle functions were associated with functional performance in older persons with LBP. Muscle functions only predicted functional performances in the older females with LBP. Kinesiophobia was associated and predicted mobility and balance in older persons with LBP. Kinesiophobia should be continuously assessed in clinical settings to recognize the obstacles that may affect patient’s compliance towards a rehabilitation program in older persons with LBP.